Study Habits, Parenting Style, and Learning Style as Correlates to Academic Performance of Students with Solo Parent - Dejarlo, Jenisus O.; Manimtim, Jannie SJ.; Padilla, Earth DP.; Juan, Jansen A. San; Aterrado, Johanne SJ. (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The Solo Parent is represented only in the family by either a mother or a father. In this age, due to different marital circumstances, many instances of solo-parenting produced a new family atmosphere with a total absence of the other. This research centered on evaluating learners' academic success, learning style, and research patterns by providing a solo parent with a different parenting style. Frequency distribution, percentage, and chi-square were used to test the sixty students found across campuses at the University of Rizal System. Results showed a strong correlation between parent identity and known parenting style to the study patterns, learning style, and subsequent academic success of the established learners, which concludes that the impact of solo parenting is affirmative for the current generation of learners.